(untitled) (Palíndromo, 2024)
Making use of the syntactic elements of design, especially colors, shapes and textures, messages are expressed through clothing that elucidate individual and collective identities and also the designer’s perspectives of the world. With the aim of showing the results of an activity carried out in a Fashion History discipline executed in a Fashion Degree course, this article intended to constitute a plot between theory and practice from the application of the contents taught in the classroom in the creative process of the students through the production of a semantic panel, and from this, to stimulate the decoding of symbolic codes for the creation of a fashion design. For this purpose, it is an applied research, with a qualitative approach and descriptive treatment. The activity was based on the methodology of meaningful learning, in which the new contents assimilated by the students are put into practice in amalgamation with those they already possessed. Thus, it can be evidenced that among the four examples presented, it is remarkable the existence of an alignment between the contents transmitted in class, the visual panels and the sketches drawn, being possible to conclude that meaningful learning was stimulated through the integration of knowledge in an integrated and transversal way.